The universe of immune deficiencies in Crohn's disease: a new viewpoint for an old disease? - Tommasini, Alberto; Pirrone, Angela; Palla, Gabriella; Taddio, Andrea; Martelossi, Stefano; Crovella, Sergio; Ventura, Alessandro (Scand J Gastroenterol, 2010)
Crohn's disease (CD) is generally considered a multifactorial disorder, since different genetic and environmental factors are thought to play a role in its pathogenesis. Recently, genome wide linkage studies allowed to identify the association of several loci with the increased risk of CD, although it is still unclear how they interact with environmental factors in causing the disease. The fact that many CD-risk-related genes are involved in the function of phagocytes seems in agreement with the well known role of these cells in CD histopathology. Functional defects in cytokine production or in clearance of bacteria in CD patients have recently been reported. Growing evidence that CD could arise from primary phagocyte immunodeficiency is also coming from the study of cases with early onset in infancy. We review such evidences starting from selected cases and discuss the clinical implications of these findings.
Keywords: Biological Markers; Crohn Disease; Cytokines; Evidence-Based Medicine; Granulomatous Disease, Chronic; Hematopoietic Stem Cell Transplantation; Humans; Immunosuppressive Agents; Phagocytes; Treatment Outcome; Wiskott-Aldrich Syndrome